2020
DOI: 10.5397/cise.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of ultrasound-guided atelocollagen injection for patients with partial rotator cuff tear in an outpatient clinic: a preliminary study

Abstract: Background: Atelocollagen has been studied for restoration of rotator cuff tendon. In this study, we attempted to evaluate the clinical outcome of ultrasound-guided atelocollagen injection in an outpatient clinic for patients with partial rotator cuff tear.Methods: We recruited 42 outpatients who visited our hospital from May 2019 to September 2019. Atelocollagen injection was performed in patients with partial rotator cuff tear diagnosed by magnetic resonance imaging and ultrasound. American Shoulder and Elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Gel-type atelocollagen is also used for ultrasonography-guided injection for partial rotator cuff tears or arthroscopic injection to the repaired rotator cuff tendon. For gel-type atelocollagen delivery, the injection is performed directly to the tear site using ultrasound in the outpatient clinics 2,15 or intraoperatively after rotator cuff repair. 12,14 Table 3 summarizes the findings of 2 level 1 randomized controlled trials that reported on clinical applications of atelocollagen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gel-type atelocollagen is also used for ultrasonography-guided injection for partial rotator cuff tears or arthroscopic injection to the repaired rotator cuff tendon. For gel-type atelocollagen delivery, the injection is performed directly to the tear site using ultrasound in the outpatient clinics 2,15 or intraoperatively after rotator cuff repair. 12,14 Table 3 summarizes the findings of 2 level 1 randomized controlled trials that reported on clinical applications of atelocollagen.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that have analyzed radiological results after ultrasound-guided injection with follow-up ultrasound or MRI. 2 , 15 In a study by Chae et al, 2 rotator cuff integrity was measured via an ultrasound performed 2 months after surgery, while muscle volume, fatty infiltration, and retear were measured at 6 months after surgery using MRI. Clear differences in tendon integrity from preinjection to postinjection were not found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the open view during surgery in our study facilitated the accurate injection of ASC-Exos/fibrin into the defect site, which could be challenging in the clinic. Nevertheless, with ultrasound guidance 26,27 , it is feasible to perform accurate injections into the defect site of the cuff tendon. Third, clinical parameters (e.g., pain, activity level, gait) were not assessed.…”
Section: Discussionmentioning
confidence: 99%